Flavor and aroma of low-dose irradiated, boneless, pork chops - Luchsinger, S.E.; Garcia Zepeda, C.M.; Chambers, Edgar, IV; Hollingsworth, M.E.; Hunt, Melvin C.; Marsden, James L.; Stroda, Sally L.; Rubio Canas, E.J.; Kastner, Curtis L.; Kuecker, W.G.; Mata, T.; Kropf, Donald H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Irradiation and irradiation source had little to no effect on flavor and aroma of boneless pork chops, either frozen or chilled. Coupled with consumer concerns about food safety and well-documented improvement in consumer attitudes about irradiated foods, irradiation of boneless pork chops has promising potential for market acceptance.
Keywords: Swine; Irradiation; Flavor; Aroma